Caring as an important foundation in coaching for social sustainability: a case study of a successful Swedish coach inhigh-performance sport - Annerstedt, C.; Lindgren, E.-C. (Reflective Practice. International and Multidisciplinary Perspectives, 2014)
The aim of this study is to describe and analyze the experiences and strategies of one successful coach in high-performance sports. Through case study methodology we have studied Bengt Johansson, one of the most successful coaches in Sweden ever. From the perspective of social sustainability, caring seems to have constituted an important basis for coaching the Swedish national team in handball during Bengt Johansson's years as head coach. Caring in this sense means to respect the players, value them, involve them, have dialogue with them, listen to them and support them as human beings. Johansson has demonstrated how competitiveness, dedication and hard work coexist alongside compassion, empathy, participation and caring